Parent Mental Health and Family Coping over Two Years after the Birth of a Child with Acute Neonatal Seizures - Linda S. Franck; Renée A. Shellhaas; Monica E. Lemmon; Julie Sturza; Marty Barnes; Trisha Brogi; Elizabeth Hill; Katrina Moline; Janet S. Soul; Taeun Chang; Courtney J. Wusthoff; Catherine J. Chu; et al. (MDPI AG, 2021)
Little is known about parent and family well-being after acute neonatal seizures. In thus study, we aimed to characterize parent mental health and family coping over the first two years after their child's neonatal seizures. Parents of 303 children with acute neonatal seizures from nine pediatric hospitals completed surveys at discharge and 12-, 18- and 24-months corrected age. Outcomes included parental anxiety, depression, quality of life, impact on the family, post-traumatic stress and post-traumatic growth. We used linear mixed effect regression models and multivariate analysis to examine relationships among predictors and outcomes. At the two-year timepoint, parents reported clinically significant anxiety (31.5%), depression (11.7%) and post-traumatic stress (23.7%). Parents reported moderately high quality of life and positive personal change over time despite ongoing challenges to family coping. Families of children with longer neonatal hospitalization, functional impairment, post-neonatal epilepsy, receiving developmental support services and families of color reported poorer parental mental health and family coping. Parents of color were more likely to report symptoms of post-traumatic stress and positive personal change. Clinicians caring for children with neonatal seizures should be aware of lasting risks to parent mental health and family coping. Universal screening would enable timely referral for support services to mitigate further risk to family well-being and child development.